Overexpression of c-erbB2 is an independent marker of resistance to endocrine therapy in advanced breast cancer - Stephen Houston; T.A. Plunkett; D M Barnes; Paul Smith; R.D. Rubens; David Miles (1999)
The present study investigated the interaction between c-erbB2 overexpression and the response to first-line endocrine therapy in patients with advanced breast cancer. The primary tumours of 241 patients who were treated at first relapse with endocrine therapy were assessed for overexpression of c-erbB2 by immunohistochemistry. c-erbB2 was overexpressed in 76 (32%) of primary breast cancers and did not correlate with any other prognostic factor. The overall response to treatment and time to progression were significantly lower in patients with c-erbB2-positive tumours compared to those that were c-erbB2-negative (38% vs 56%, P = 0.02; and 4.1 months vs 8.7 months, P < 0.001, respectively). In multivariate analysis, c-erbB2 status was the most significant predictive factor for a short time to progression (P = 0.0009). In patients with ER-positive primary tumours treated at relapse with tamoxifen (n = 170), overexpression of c-erbB2 was associated with a significantly shorter time to progression (5.5 months vs 11.2 months, P < 0.001). In conclusion, overexpression of c-erbB2 in the primary tumour is an independent marker of relative resistance to first-line endocrine therapy in patients with advanced breast cancer. In patients with ER-positive primary tumours, the overexpression of c-erbB2 defines a subgroup less likely to respond to endocrine therapy.